Prevalence of posterior vitreous detachment detected by ultrasound in Erbil governorate - Abdulghani, Hussein Ismail; Rashid, Sameeah A.; Abdulghani, Ahmed Ismail (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Posterior vitreous detachment is a common problem which may induce several potentially serious events. The aim of the study was to determine the prevalence of posterior vitreous detachment in Erbil and its distribution among different age groups also to determine its correlation to age, gender, smoking, blurring of vision, floater, flashes of light, diabetes mellitus and hypertension.Methods: A cross-sectional study carried out on 150 persons (300 eyes) with mean age of 40 years attending Rizgary Teaching Hospital (Erbil, Iraq) who were referred for ultrasound examination for any indication other than eye problem. The patients were examined by ocular ultrasound unit equipped with a 7.5–10 MHz real-time linear high-frequency probe with the contact method.Results: The prevalence of posterior vitreous detachment was 19.3%, with an extremely statistical significant association between posterior vitreous detachment and increasing age, diabetes, hypertension, blurred vision and floater, but no association with smoking, gender and flash of light.Conclusion: Posterior vitreous detachment is a common disease its prevalence increases with advancing age with a strong association to blurred vision, floaters, diabetes mellitus and hypertension but no association with gender, smoking or ultrasound detected vitreous opacities.